Legal Review of Legal Protection for Communities Affected by Land Acquisition for Public Interest under Law No. 2 of 2012 on Land Acquisition for Development in the Public Interest - Saniah Saniah (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the legal protection available to communities affected by land acquisition for public interest development in Indonesia. Although governed primarily by Law No. 2 of 2012 and updated through Law No. 6 of 2023, many legal ambiguities remain, especially regarding the fairness of compensation and the recognition of informal or uncertified land rights. The objective of this study is to critically evaluate the adequacy of these legal frameworks and identify gaps that undermine justice for affected populations. Employing a normative-juridical method, the research conducts doctrinal analysis, comparative law review (with cases from Malaysia and India), and stakeholder consultation to assess both the text and implementation of relevant laws. The study finds that key legal concepts such as “fair and appropriate compensation” remain undefined in statute, leading to inconsistent application across regions. Furthermore, compensation mechanisms such as share ownership and resettlement are inadequately regulated and poorly implemented. The findings emphasize the disparity between normative intent and administrative reality, particularly for holders of uncertified land. By integrating stakeholder feedback with normative evaluation, the research proposes actionable reforms to strengthen legal protection and uphold constitutional guarantees under Article 28H. In conclusion, while Indonesia has made progress in establishing a framework for public interest land acquisition, significant doctrinal and institutional reforms are required to ensure equitable outcomes for all landholders.